Renewable energy barriers and coping strategies: Evidence from the Baltic States. (23rd December 2019) - Lu, Jintao; Ren, Licheng; Yao, Siqin; Rong, Dan; Skare, Marinko; Streimikis, Justas
Abstract: Renewable energy sources (RES) are the main drivers of sustainable energy development. Notwithstanding the substantial expansion of renewables in the past decade, boosted by the various policies and measures, renewable energy sources are still far from full incorporation into the energy markets. It is necessary to overcome the remaining impediments for renewables to realize the energy transition to 100% renewable energy. The aim of this research is to analyze the main barriers of renewables and success of policies dealing with these barriers. The case studies in the Baltic States provide concrete examples of policies and their impacts in terms of overcoming barriers in relevant sectors: heating and cooling, power and transport. The assessment of policies in the Baltic States shows that there are a few measures that are implemented in the transport sector, although this sector encounters many social, economic, technological, and regulatory barriers. The countries have achieved the lowest results in approaching RES targets in transport. New financial incentives and investments in the development of infrastructure for electric vehicles are crucial for the development of markets of electric vehicles.